Soil application of Meliaceae derivatives: effect on carbon and nitrogen dynamics in the soil-plant system - Marcolini, Graziella <1977> (Alma Mater Studiorum - Università di Bologna, 2013)
The effect of soil incorporation of 7 Meliaceae derivatives (6 commercial neem cakes and leaves of Melia azedarach L.) on C and N dynamics and on nutrient availability to micropropagated GF677 rootstock was investigated. In a first laboratory incubation experiment the derivatives showed different N mineralization dynamics, generally well predicted by their C:N ratio and only partly by their initial N concentration. All derivatives increased microbial biomass C, thus representing a source of C for the soil microbial population. Soil addition of all neem cakes (8 g kg-1) and melia leaves (16 g kg-1) had a positive effect on plant growth and increased root N uptake and leaf green colour of micropropagated plants of GF677. In addition, the neem cakes characterized by higher nutrient concentration increased P and K concentration in shoot and leaves 68 days after the amendment. In another experiment, soil incorporation of 15N labeled melia leaves (16 g kg-1) had no effect on the total amount of plant N, however the percentage of melia derived-N of treated plants ranged between 0.8% and 34% during the experiment. At the end of the growing season, about 7% of N added as melia leaves was recovered in plant, while 70% of it was still present in soil. Real C mineralization and the priming effect induced by the addition of the derivatives were quantified by a natural 13C abundance method. The real C mineralization of the derivatives ranged between 22% and 40% of added-C. All the derivatives studied induced a positive priming effect and, 144 days after the amendment, the amount of C primed corresponded to 26% of added-C, for all the derivatives. Despite this substantial priming effect, the C balance of the soil, 144 days after the amendment, always resulted positive.